RETRACTED: 3-year results of hop hybrids testing - Dementiev D.A.; Fadeev A.A. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001